1963
DOI: 10.1083/jcb.16.2.297
|View full text |Cite
|
Sign up to set email alerts
|

On the Structural Continuities of the Transverse Tubular System of Rabbit and Human Myocardial Cells

Abstract: An electron microscopic study of rabbit and human myocardium provides further evidence of the existence of two distinct components of the sarcoplasmic reticulum. A thin-walled tubular system (termed longitudinal system) is arranged in anastomosing channels sursurrounding each sarcomere and has transverse and possibly also longitudinal connections with the tubules of adjacent sarcomeres. A thick-walled tubular system traverses the myofiber transversely at the level of the Z lines of the myofibrils. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

1964
1964
1968
1968

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(45 citation statements)
references
References 27 publications
2
42
1
Order By: Relevance
“…Variations in the amount of calcium released during excitation-contraction coupling would be expected to modify myocardial contractility and shortening velocity if the heart's contraction is normally limited by the availability of intracellular calcium. The latter view is supported by the finding that the cardiac sarcoplasmic reticulum, which is presumed to contain this calcium, is less extensive than that of skeletal muscle (48)(49)(50). Because the sensitivities of cardiac and skeletal actomyosins to changing levels of Ca ++ are similar (42,43,51), these anatomical findings indicate that the heart's sarcoplasmic reticulum may normally contain less calcium than is needed to activate the cardiac actomyosin fully.…”
Section: Cardiac Actomyosinsupporting
confidence: 64%
“…Variations in the amount of calcium released during excitation-contraction coupling would be expected to modify myocardial contractility and shortening velocity if the heart's contraction is normally limited by the availability of intracellular calcium. The latter view is supported by the finding that the cardiac sarcoplasmic reticulum, which is presumed to contain this calcium, is less extensive than that of skeletal muscle (48)(49)(50). Because the sensitivities of cardiac and skeletal actomyosins to changing levels of Ca ++ are similar (42,43,51), these anatomical findings indicate that the heart's sarcoplasmic reticulum may normally contain less calcium than is needed to activate the cardiac actomyosin fully.…”
Section: Cardiac Actomyosinsupporting
confidence: 64%
“…Recent electron microscopy studies (11,12) have demonstrated that the sarcolemma is a complex structure that consists of as many as four separate layers not only surrounding the myofiber but also forming an extensive connecting system around and between the individual myofibrils. The subsarcolemmal and intermyofibrillar areas also contain sarcoplasmic components and mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…In heart muscle, for example, invaginations of the sarcolemma have been demonstrated in several cases to penetrate into the fiber (11,36,55,56). Since these start at the periphery of the fiber at the Z line level and run at this level across the fiber for at least a few microns, their homology with the T system is evident.…”
Section: Interpretation Of the New Image Of The T Systemmentioning
confidence: 97%